ANALYSIS OF GAS PIPELINE INTEGRITY CROSSING HIGHWAYS, RAILROADS AND RIVER (CASE STUDY: TAMBUN ÃâÃâ PONDOK TENGAH ÃâÃâ TEGAL GEDE GAS PIPELINE) - PERDANA (NIM : 13104136); Pembimbing : Prof. Dr. Ir. IGN Wiratmaja Puja, ADITIA
Process transmission of oil and gas, especially at onshore, does not only pass through some remote area but also populous area. Pipeline can also meet various obstacle like cross over highways, railroads, river, or homesite. Stress analysis needs to be done for the pipeline that is going through the obstacle to obtain the stresses that occur at each crossing point and the status of the feasibility of those pipelines. Program development has been done on this final project based on API RP 1102. The purpose of this program is used to simplify the calculation of stress analysis at pipeline cross over highways and railroads. The author analyzes various kind of stress at pipeline in all 55 pipeline crossing point of highways and 1 point railroads crossing for Tambun – Pondok Tengah – Tegal Gede Gas Pipeline and make selection according to the apropriate casing pipe. This final project determine crossing methods also, including 10 point river crossing. Stress analysis result that has been done shows that for all locations of highways crossing have stress rasio < 1, so it is safe, while for railroad crossing has the highest stress rasio 1.68 so it is not safe. It is recommended, therefore, usage of casing pipeline for a pipeline cross over railroads with NPS 24 in and wall thickness 0.312 in. The selection of appropriate crossing method must be considered carefully to reduce the occurence of environmental damage.